The lifelong learner in cognitive capitalism: the ability-capital machine and the production of neurotic citizens - Kinnari, Heikki; Laalo, Hanna; Silvennoinen, Heikki (Informa UK Limited, trading as Taylor & Francis Group., 2026)
In contemporary lifelong learning policies by the OECD and the European Union, citizens are expected to acquire knowledge, skills and attitudes that are believed to enhance individual, social and economic well-being. This article examines the current ideal of lifelong learner constructed in these policies from a governmentality perspective. The central object of theorisation is the concept of the ability-capital machine, which is introduced as a heuristic device to capture how lifelong learning policy constructs the ideal subject in the context of cognitive capitalism. This concept allows for the analysis of how subjectivities are shaped through the standardisation of competences, the demand for emotional and attitudinal reflectivity, and the promotion of self-optimisation. Additionally, drawing on the notion of neuroliberalism, the analysis explores how individual traits, emotions, and psychological attributes are brought under governing through neuroscientific and behavioural discourses in lifelong learning policies. Finally, the notion of the neurotic citizen is introduced to describe the unintended yet systemic consequences of these policies. It is contended that policies based on key competencies in lifelong learning not only construct and govern an emancipated and self-directed ability-capital machine but also evoke a self-concerned and anxious one: a neurotic lifelong learner.